Unravelling the molecular cues of plant adaptation or survival to water deficit - Ambrosone A.; Costa A.; Frusciante L.; Monti L.; Leone A.; Grillo S. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
When experiencing water deficit, glycophyte plants undergo physiological and biochemical changes aimed at limiting cellular damages and rescuing a new cellular homeostasis. Discriminate irreversible cell injury from adaptive rearrangements to water stress, is quite critical since only the latter plant response is compatible with active growth and development sustaining, ultimately, plant yield. An up-dated view of the molecular basis of cellular response to drought stress and of key functions activated able to protect cellular processes is summarized in the paper. It also reported a functional approach developed to identify genes with a crucial role in the adaptation to water deficit based on the systematic comparison of potato cell populations exposed abruptly or gradually to PEG-induced low water potential. Gradually adapted cells were characterized by distinctive metabolic adaptations (proline accumulation, changes in membrane lipid composition, de novo synthesis, etc) which enable them to grow actively at non-permissive water stress conditions. Differential gene expression in response to shock or gradually increasing water deficit was monitored by microarray technology, using the 1K TIGR potato cDNA array. More than 100 genes belonging to different functional categories were up-regulated in response to stress conditions. However, only a few induced genes were common to both cell populations, confirming that different gene networks mediate shock or long-term response to water deficit.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)